2011
DOI: 10.1159/000333378
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trypsin Inhibitor Attenuates Seawater-Induced Acute Lung Injury by Influencing the Activities of Nuclear Factor-ĸB and Its Related Inflammatory Mediators

Abstract: Background: Few data are available on the role of neutrophil elastase (NE) and nuclear factor-ĸB (NF-ĸB) in the course of seawater drowning-induced acute lung injury (SWD-ALI), and there is no evidence on the value of giving urinary trypsin inhibitor (UTI) in the case of SWD-ALI. Objective: To investigate the role of NF-ĸB and NE in the pathogenesis of SWD-ALI and whether UTI treatment can attenuate SWD-ALI in rabbits. Methods: Rabbits were randomly assigned to control, seawater drowning, and UTI treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
1
14
1
Order By: Relevance
“…In addition, the excessive inflammatory response in seawater-induced ALI is characterized by the transmigration of neutrophils into the lung interstitial and the alveolar space, which in turn release numerous pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6. Among the potent mediators, NF-κB pathway plays a pivotal role in the pro-inflammatory cytokines production in many inflammatory diseases and the activation of this pathway is also a crucial component in seawater aspiration-induced ALI [13,27]. It has been previously described that cytokines induced degradation of IkBs, which subsequently can induce NF-κB p65 and translocation from the cytoplasm to the nucleus where they bind with the target genes and regulate their transcription [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the excessive inflammatory response in seawater-induced ALI is characterized by the transmigration of neutrophils into the lung interstitial and the alveolar space, which in turn release numerous pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6. Among the potent mediators, NF-κB pathway plays a pivotal role in the pro-inflammatory cytokines production in many inflammatory diseases and the activation of this pathway is also a crucial component in seawater aspiration-induced ALI [13,27]. It has been previously described that cytokines induced degradation of IkBs, which subsequently can induce NF-κB p65 and translocation from the cytoplasm to the nucleus where they bind with the target genes and regulate their transcription [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ulinastatin inhibits pathogenic changes in animal models of ALI/ARDS induced by many factors (including scald, seawater, LPS, phosgene) [6][7][8][9] . Immunoregulation and the mitigation of excessive inflammatory reaction might be involved.…”
Section: Leng Yx Et Al a Systematic Review Of Ali And Ardsmentioning
confidence: 99%
“…The lung wet/dry weight (W/D) ratio was used to assess pulmonary edema [17,22]. Right lower lungs were isolated for determination of the W/D ratios.…”
Section: Methodsmentioning
confidence: 99%